Association between Soil Acidity and Bacterial Wilt Occurrence in Potato Production in Ethiopia - Tafesse, S.; Braam, C.; Mierlo, B. van; Lemaga, B.; Struik, Paul C. (MDPI, 2021)
Soil acidity is one of the main constraints to crop production worldwide. In Ethiopia, the problem of soil acidity has been increasing. Currently, more than 40% of cultivated land in the country has a soil pH < 5.5. Recently, bacterial wilt (caused by Ralstonia solanacearum) has become a serious problem, reaching epidemic levels in some of the major potato growing districts in the country. However, it is currently unknown if the current outbreak of bacterial wilt in potato production is associated with soil acidification or not. To examine the association between bacterial wilt and soil acidification, we conducted a field survey and field experiments and detected and characterised R. solanacearum strains. The study showed that 50% of potato fields were very strongly acidic (pH 4.5–5.0) and bacterial wilt incidence was higher in potato fields with low soil pH. The field experiments indicated that lime application significantly increased soil pH (p < 0.001) and reduced bacterial wilt incidence (p < 0.001). The more lime was applied, the stronger the positive effect on soil pH and the stronger the reduction in bacterial wilt incidence. Bacterial wilt incidence was on average 10.8% under 12 t/ha lime application, while it was about 40% in control plots (without lime) after 90 days. All R. solanacearum strains isolated from the symptomatic potato plants were Phylotype II. Our findings show that the current outbreak of bacterial wilt in Ethiopia is associated with soil acidification. They add to the understanding of the risk factors for bacterial wilt in potato. Aside from farm hygiene, sanitation and cultural practices, addressing soil acidification using lime needs to be considered as an additional component of an integrated package to deal with bacterial wilt in potato under acidic soil conditions.